Microstructure and magnetic properties of Nd-Fe-B permanent magnets produced by laser powder bed fusion. (August 2021) - Bittner, F.; Thielsch, J.; Drossel, W.-G.
Abstract: Additive manufacturing of Nd-Fe-B is a novel approach for the fabrication of permanent magnets. We present an analysis of the magnetic properties and microstructure of Nd-Fe-B permanent magnets, which were produced by laser powder bed fusion (LPBF). By optimization of processing parameters for the Nd-lean powder coercivity of 921 kA/m (1.16 T), remanence of 0.63 T and maximum energy product of 63 kJ/m 3 are achieved without the addition of further Nd-rich low-melting alloys or any other post treatment. Thereby, remanence and maximum energy product represent the highest reported values for additively manufactured permanent magnets. The impact of area energy density EA on the magnetic properties is discussed. The isotropic microstructure consists of short Nd2 Fe14 B dendrites at the melt pool boundaries and globular sub-micron sized grains in the melt pool interior. After LPBF of the Nd-lean powder no evidence of α-Fe is found in the microstructure. Graphical abstract: Image, graphical abstract